"Niveles de inclusión de harina de cáscara de maracuyá (Passiflora edulis) en el engorde de cuyes sexados (Cavia Porcellus Linnacus)". - Moreira Suárez, Diego Fernando (2020)
The research was carried out in the Experimental Campus "La María" of the State Technical University of Quevedo (UTEQ), located at km. 7½ of the Quevedo-El Empalme road, Mocache Canton, Los Ríos Province, whose geographical location is 1 ° 3'18 ”south latitude and 79 ° 25 '24' 'west longitude, at a height of 77.60 masl , with a duration of 42 days. The objectives being: To determine the productive behavior in the fattening of sexed guinea pigs, fed with increasing levels of passion fruit peel flour (0; 10; 20 and 30%) and the profitability of the treatments. A factorial arrangement 2 (sex) x 4 (levels of inclusion of passion fruit flour in the diet) was applied within a randomized complete block design (DBCA), the initial weight of the experimental units (EU) was blocked, with Five repetitions To determine the differences between treatment means, the Tukey test (P≤0.05). 40 guinea pigs (20 males and 20 females) of 30 days of age were used, with an average weight of 267.18 g. Feed consumption (g), weight gain (g), feed conversion rate, carcass weight (g), carcass yield (%) and profitability were evaluated through the Cost Benefit Ratio. The sexual condition (male-female) did not affect the productive response of the guinea pigs (P˃0.05). The inclusion levels of passion fruit flour did not influence (P> 0.05) on the final weight, weight gain, food consumption, feed conversion rate and carcass weight, except carcass yield, being higher (P <0.05) with the inclusion level of 40% (66.75). Keywords: Food, flour, nutrition, guinea pigs, diets, passion fruit.